2011
DOI: 10.1126/science.1210027
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Size Affects Neural Circuits in Macaques

Abstract: It has been suggested that variation in brain structure correlates with the sizes of individuals' social networks. Whether variation in social network size causes variation in brain structure, however, is unknown. To address this question, we neuroimaged 23 monkeys that had been living in social groups set to different sizes. Subject comparison revealed that living in larger groups caused increases in gray matter in mid-superior temporal sulcus and rostral prefrontal cortex and increased coupling of activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
379
3
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(417 citation statements)
references
References 32 publications
27
379
3
8
Order By: Relevance
“…Yet, once proficient, such individuals show tool use with high degrees of automatization. Secondary modularization is also supported by plastic changes in the brain, such as the changes in gray matter content of parts of the neocortex of rhesus monkeys in response to changes in social group size [47].…”
Section: Domain-specific or Domain-general Cognitive Abilities?mentioning
confidence: 99%
“…Yet, once proficient, such individuals show tool use with high degrees of automatization. Secondary modularization is also supported by plastic changes in the brain, such as the changes in gray matter content of parts of the neocortex of rhesus monkeys in response to changes in social group size [47].…”
Section: Domain-specific or Domain-general Cognitive Abilities?mentioning
confidence: 99%
“…To address this question, Sallet et al [8] experimentally assigned male rhesus macaques to social groups of different sizes and later scanned their brains with MRI. There were significant positive associations between social network size and grey matter thickness in mid-STS, rostral STS, inferior temporal (IT) gyrus, rostral prefrontal cortex (rPFC), temporal pole and amygdala.…”
Section: Mechanisms Mediating the Evaluation Of Social Partners' Valumentioning
confidence: 99%
“…These findings indicate that natural selection has favoured individuals that are equipped with the cognitive architecture to navigate a social world in which they must make rapid decisions about when to compete and when to cooperate and when and whether to involve themselves in a given social interaction. We are only beginning to understand the precise neural and hormonal mechanisms that mediate adaptive decision-making in animals, and the degree to which such abilities vary among individuals remains largely unexplored [2,6,[8][9][10][11][12]. We also still have little understanding about the extent to which such variation is heritable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study of this kind showed that lonely individuals have less posterior superior temporal cortex gray matter volume and at the same time deficits in basic social perception skills; the latter two variables were themselves found to be correlated (Kanai et al 2012a). A number of further studies have reported a positive correlation between social network size and gray matter volume in socio-emotional brain regions including the amygdala and the posterior superior temporal cortex (Bickart et al 2011;Sallet et al 2011;Kanai et al 2012b). …”
mentioning
confidence: 99%